Analysis of ‘Urf on the Makkappa’ Tradition among the Pattae Community in Polewali Mandar - Arman; Ahmad; Naharuddin SR; Faisal Nur Shadiq Shabri (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2026)
This study explores the Makkappa’ tradition among the Pattae community in Polewali Mandar Regency, analyzing its alignment with the Islamic legal concept of 'urf sahih (valid custom). Makkappa’, practiced before Ramadan, involves communal prayers, shared meals, and social gatherings, fostering unity, gratitude, and spiritual readiness. The research employs a qualitative ethnographic approach, using interviews, participant observation, and documentary analysis to examine how Makkappa’ reflects Islamic values while preserving cultural identity. Findings reveal that Makkappa’ strengthens social cohesion, promotes intergenerational bonding, and supports cultural sustainability without contradicting Sharia. This tradition exemplifies the harmonious integration of local culture and Islamic principles, contributing to a resilient Pattae identity.